PELATIHAN STRATEGI CORPORATE BRANDING PENGUSAHA MELALUI KONTEN - Detya Wiryany; Rizky Surya Tawaqal; arie hendra saputro (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
MSME actors have quite big challenges to survive and grow with the current state of affairs,as well as increasingly fierce competition in the business and creative world. The current conditionsare also a challenge that is not easy during this pandemic, MSMEs are increasingly squeezed by thecondition of declining consumer buying interest in MSME products. MSMEs today must be digitallyliterate, this is to accelerate brand growth so that it is easily recognized by the public. According todata from "Hootsuite" internet users in Indonesia touch 202.6 million users, while 170 millionactive social media users are data for 2021. Brand strength can provide customer loyalty, financialbenefits, and the foundation for developing new products and markets. All successful businessesmust have the main steps to build a brand, because without efforts to build a brand, the product hasno value in the eyes of consumers. Virageawie Indonesia already has an active social media accountbut requires branding that is quite focused on marketing its brand products. For this reason, in thisactivity proposal, the team will assist Virageawie Indonesia as a fostered partner at the Universityof Indonesia Mebangun to revive the Virageawie Indonesia/Indonesian Bamboo Community productbrand in creating focus and developing corporate branding.